2022
DOI: 10.1097/phh.0000000000001590
|View full text |Cite
|
Sign up to set email alerts
|

Successful Hepatitis C Birth Cohort Screening and Linkage to Care in a US Community Health System

Abstract: Context: Birth cohort ("baby boomer") screening represents a well-validated strategy for the identification of asymptomatic hepatitis C-infected patients. However, successful linkage of newly diagnosed patients to antiviral therapy has been more difficult to accomplish. Objective: To analyze the results of a systemwide birth cohort screening program in a US community health care system. Design: We analyzed the data from an ongoing hepatitis C virus (HCV) screening and treatment program that was established at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Given the limitations of a risk-based approach to screening and their own experiences of having no symptoms attributable to hepatitis C, participants described the importance of considering broader population-based screening strategies for identifying asymptomatic individuals otherwise perceived as being at minimal risk for hepatitis C. Notably, through their participation in the focus groups, participants identified older adults as being one potential group that could benefit from enhanced screening programs, an observation that is consistent with birth-cohort screening strategies endorsed as a means of identifying undiagnosed individuals [ 50 , 51 ]. P: There may be a certain age group of people, I don’t know, that might be, I don’t know.…”
Section: Resultsmentioning
confidence: 87%
“…Given the limitations of a risk-based approach to screening and their own experiences of having no symptoms attributable to hepatitis C, participants described the importance of considering broader population-based screening strategies for identifying asymptomatic individuals otherwise perceived as being at minimal risk for hepatitis C. Notably, through their participation in the focus groups, participants identified older adults as being one potential group that could benefit from enhanced screening programs, an observation that is consistent with birth-cohort screening strategies endorsed as a means of identifying undiagnosed individuals [ 50 , 51 ]. P: There may be a certain age group of people, I don’t know, that might be, I don’t know.…”
Section: Resultsmentioning
confidence: 87%
“…The US Department of Health and Human Services found that from 2013 to 2016, only 32% of chronic HBV carriers were aware of their infection contributing to the underdiagnosis of cirrhosis and HCC [40]. Increased screening efforts for HCV across communities in the USA, including the Northshore University Health System, resulted in successfully screening 64.3% of the eligible population born between 1945 and 1965 [41].…”
Section: Five Pillars For Hbv Elimination 1st Pillar: Hbv Screening D...mentioning
confidence: 99%